An energy-efficient smart city for sustainable green tourism industry. (October 2021) - Lu, Chun-Wei; Huang, Jui-Chan; Chen, Chen; Shu, Ming-Hung; Hsu, Chih-Wei; Tapas Bapu, B.R.
Abstract: In recent times, Tourism and Travel are considered a flexible, dynamic, and ever-growing industry. The Smart Tourism Destinations concept arises from the advancement of smart cities. Since information technologies are considered a key competitive element of a city's destination, tourism companies invest extensively in smart system initiatives. Moreover, the smart city concept and related approaches are increasingly recognized by cities worldwide to optimize sustainable environments. Furthermore, a smart tourist city faces the challenge of creating urban areas that residents and tourists can experience together, particularly in cities that pose new tourism challenges. This paper proposes the Data-Driven Sustainable Smart City Framework (DDSSCF) for sustainable green tourism strategies and policies. This paper explores the aspects of technologies essential for creating a smart city and a fashionable tourism destination. The preservation of the climate, protected cultural heritage, and natural resources would contribute to an environment, the economic, social sustainable field of tourism by reducing hazardous pollutants and energy usage. Therefore, based on the preservation limit, it has been classified into three components includes-green architecture, green waste, and green energy as a part of the green management framework at the same time. Hence, green tourism, including marketing efforts, such as green marketing, are necessary for the vision of successful adequate green management activities. The experimental results show that the proposed method enhances efficiency ratio when compared to other existing methods.